1994
DOI: 10.1161/01.res.75.4.650
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix remodeling after balloon angioplasty injury in a rabbit model of restenosis.

Abstract: Remodeling of the vessel wall after balloon angioplasty injury is incompletely understood, and in particular, the role of extracellular matrix synthesis in restenosis has received little attention. The objective of the present study was to determine the sequence of changes in collagen, elastin, and proteoglycan synthesis and content after balloon injury and to relate these changes to growth of the intimal lesions and extent of cell proliferation. In a double-injury non-cholesterol-fed model, right iliac arteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
162
0
4

Year Published

1996
1996
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(179 citation statements)
references
References 43 publications
10
162
0
4
Order By: Relevance
“…SDF-1␣ binding to proteoglycans has been described recently to enhance SDF-1␣-induced migration of hematopoietic progenitor cells. 22 Because proteoglycan synthesis is increased after balloon angioplasty and therefore proteoglycans contribute significantly to extracellular matrix in neointimal lesions, 23 SDF-1␣ may be released into the circulation early after endothelial denudation but could be bound to proteoglycans in the developing neointimal matrix, thereby shifting its contribution from early mobilization toward a more continuous neointimal recruitment of PBPCs. Beyond its effects on recruitment within the first weeks, local SDF-1␣ may further affect the neointimal SMC architecture, thus contributing to arterial remodeling of injured vessels.…”
Section: Discussionmentioning
confidence: 99%
“…SDF-1␣ binding to proteoglycans has been described recently to enhance SDF-1␣-induced migration of hematopoietic progenitor cells. 22 Because proteoglycan synthesis is increased after balloon angioplasty and therefore proteoglycans contribute significantly to extracellular matrix in neointimal lesions, 23 SDF-1␣ may be released into the circulation early after endothelial denudation but could be bound to proteoglycans in the developing neointimal matrix, thereby shifting its contribution from early mobilization toward a more continuous neointimal recruitment of PBPCs. Beyond its effects on recruitment within the first weeks, local SDF-1␣ may further affect the neointimal SMC architecture, thus contributing to arterial remodeling of injured vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Because of these findings, we investigated the effects of tranilast on the PDGF-induced VSMC migra tion and proliferation. Also, we observed the VSMC syn thesis of collagen, a protein component of the extracel lular matrix, because it is reported that the accumulation of collagen produced by VSMCs is one of the causes of the intimal hyperplasia (2,28). In this study, tranilast inhibited both PDGF-induced VSMC migration and proliferation.…”
Section: Discussionmentioning
confidence: 97%
“…These cytokines induce VSMC migration from the media to the intima and VSMC proliferation there. The VSMCs that have migrated and proliferated not only release cytokines, which make other VSMCs migrate and proliferate, but also produce an extracellular matrix (2)(3)(4). The precise mechanism of intimal hyperplasia in the perivascular manipulation model is yet unknown; However, it is reported that leukocytes accumulate in the intima of the perivascularly manipulated area, where their products cause endothelial denudation (20, 27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 The arterial remodelling 9 in restenosis pathophysiology has further fuelled the interest in understanding matrix changes after balloon arterial injury. Collagen, the most abundant ECM protein accumulated after balloon injury, 3 may be an important factor in development of stenosis and restenosis. Recently, considerable effort has been devoted to exploring the role of the renin-angiotensin-aldosterone system (RAAS) in vascular proliferative responses to injury.…”
Section: Introductionmentioning
confidence: 99%